Comparing identified and statistically significant lipids and polar metabolites in 15‐year old serum and dried blood spot samples for longitudinal studies. (15th March 2017) - Kyle, Jennifer E.; Casey, Cameron P.; Stratton, Kelly G.; Zink, Erika M.; Kim, Young‐Mo; Zheng, Xueyun; Monroe, Matthew E.; Weitz, Karl K.; Bloodsworth, Kent J.; Orton, Daniel J.; Ibrahim, Yehia M.; Moore, Ronald J.; et al.
Abstract : Rationale: The use of dried blood spots (DBS) has many advantages over traditional plasma and serum samples such as the smaller blood volume required, storage at room temperature, and ability to sample in remote locations. However, understanding the robustness of different analytes in DBS samples is essential, especially in older samples collected for longitudinal studies. Methods: Here we analyzed the stability of polar metabolites and lipids in DBS samples collected in 2000‐2001 and stored at room temperature. The identified and statistically significant molecules were then compared to matched serum samples stored at –80°C to determine if the DBS samples could be effectively used in a longitudinal study following metabolic disease. Results: A total of 400 polar metabolites and lipids were identified in the serum and DBS samples using gas chromatograph/mass spectrometry (GC/MS), liquid chromatography (LC)/MS, and LC/ion mobility spectrometry‐MS (LC/IMS‐MS). The identified polar metabolites overlapped well between the sample types, though only one statistically significant metabolite was conserved in a case‐control study of older diabetic males with low amounts of high‐density lipoproteins and high body mass indices, triacylglycerides and glucose levels when compared to non‐diabetic patients with normal levels, indicating that degradation in the DBS samples affects polar metabolite quantitation. Differences in the lipid identifications indicated that some oxidation occurs in the DBS samples. However, 36 statistically significant lipids correlated in both sample types. Conclusions: The difference in the number of statistically significant polar metabolites and lipids indicated that the lipids did not degrade to as great of a degree as the polar metabolites in the DBS samples and lipid quantitation was still possible. Copyright © 2016 John Wiley & Sons, Ltd.